Perceived Risks, Reliability and Service Quality in Nepal’s E-Banking Service: An Insight into Customer Perception - Bhandari, Badri Prasad; Palli , Dan Bahadur; Chaulagain, Rajesh Kumar (JMC Research Journal, 2025)
This study investigates customer perception of e-banking services in Nepal within Nepalese commercial banks, focusing on perceived usefulness, quality of services and reliability as critical determinants. Utilizing a quantitative methods approach encompassing both descriptive and causal research designs, data were collected through structured surveys administered to 390 digital banking users across various banks in Nepal. Statistical tools, including correlation and regression analysis, were employed to explore the relationships among these variables. The findings revealed significant positive correlations between customer satisfaction and perceived usefulness as well as between customer attitudes. The regression analysis model demonstrates a moderate positive correlation with reliability, perceived usefulness and quality of Service. These insights deepen the understanding of customer behaviors and preferences in digital banking, offering actionable recommendations to enhance service quality and promote financial inclusion initiatives in Nepal. This research contributes to advancing the discourse on digital banking’s role in customer-centered banking environments, providing valuable insights for policymakers, regulators, and banking institutions seeking to optimize customer satisfaction and engagement in the evolving digital landscape.